Development and manifestation of behavior problems and risk behavior among Icelandic youth - Sandra Sif Sæmundsdóttir 1990- (2019)
The majority of children and adolescents that show risk behavior, such as substances use and participate in antisocial and criminal activity, exhibit behavior problem in early childhood. These children are more likely to meet diagnostic criteria for disruptive disorders (e.g. ADHD, Oppositional Defiant Disorder (ODD) and Conduct disorder (CD)). In addition, ODD has been found to be strongly associated with later Conduct disorder and criminal activity. A growing body of evidence suggests that the seriousness, duration and consequences that stem from behavior problems are associated with early onset. Thus, it is important to intervene when behavior problems are apparent. Early intervention increases the likelihood of preventing further development of problem behavior and the development of conduct disorder. The purpose of this study was to gather information about children/adolescence at-risk in Iceland and assess if diagnosis and age of onset of behavior problems were related to earlier onset of substance use and delinquent behavior as well as assess the perceived usefulness of implemented treatments and if the perceived usefulness differ for different diagnosis. A questionnaire was administered to parents or legal guardians of children that have shown risk behavior in Iceland. Majority of participants were first aware of their children behavior problem before the age of 8. Those diagnosed with ODD where significantly more likely to have onset of behavior problem before the age of 8 years old and where more likely to have earlier onset of substance use and delinquency. Parents and legal guardians of high-risk youth did not perceive implemented treatments to be useful.